AL-QUR’AN DAN KONSELING - Irwan S (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
The Qur'an as a Muslim holy book does not only contain religious teachings (worship). It turns out that in the verses there are many lessons relating to science that are currently developing. Among these is that in the Qur'an there are found many studies that also discuss the themes discussed by counseling. This article, among others, tries to inform or can be said to reveal some of the verses that have a relationship with the themes of counseling in question.Keywords: Al-Qur'an verses and counseling.